(untitled) (Research, Society and Development, 2020)
Breastfeeding is a multifactorial process that both benefits mother and child. The promotion of exclusive breastfeeding up to six months of age is essential to reduce infant morbidity and mortality. In this context, the nursing professional acts to promote information and encourage breastfeeding since the beginning of pregnancy and promotes the application of appropriate techniques for satisfactory breastfeeding. Given the relevance of the topic, the objective of the present study was to conduct a qualitative bibliographic survey about the performance of the nursing professional in the breastfeeding process. To this end, a search was conducted in the main scientific databases using the keywords: Breastfeeding, nursing, breastfeeding, nurse. The review was structured to present the importance of breastfeeding in the health of the mother and child, the role of nurses in this process and the advancement of public breastfeeding policies in Brazil. With this, the present work can conclude that the importance of exclusive breastfeeding until the child six months of age is unanimous in the literature and that the nursing professional has a decisive role in the adequate application of techniques and stimuli regarding the breastfeeding process appropriate.